Cost-effectiveness of dipeptidyl peptidase-4 inhibitor monotherapy versus sulfonylurea monotherapy for people with type 2 diabetes and chronic kidney disease in Thailand - Permsuwan U. (2017)
© 2016 Informa UK Limited, trading as Taylor & Francis Group. Objective: With a high prevalence of chronic kidney disease (CKD) in type 2 diabetes (T2DM) in Thailand, the appropriate treatment for the patients has become a major concern. This study aimed to evaluate long-term cost-effective of dipeptidyl peptidase-4 (DPP-4) inhibitor monothearpy vs sulfonylurea (SFU) monotherapy in people with T2DM and CKD. Methods: A validated IMS CORE Diabetes Model was used to estimate the long-term costs and outcomes. The efficacy parameters were identified and synthesized using a systematic review and meta-analysis. Baseline characteristics and cost parameters were obtained from published studies and hospital databases in Thailand. Costs were expressed in 2014 US Dollars. Outcomes were presented as an incremental cost-effectiveness ratio (ICER). One-way and probabilistic sensitivity analyses were performed to estimate parameter uncertainty. Results: From a societal perspective, treatment with DPP-4 inhibitors yielded more quality-adjusted life years (QALYs) (0.024) at a higher cost ( > 66,000 Thai baht (THB) or > 1,829.27 USD) per person than SFU, resulting in the ICER of > 2.7 million THB/QALY ( > 74,833.70 USD/QALY). The cost-effectiveness results were mainly driven by differences in HbA1c reduction, hypoglycemic events, and drug acquisition cost of DPP-4 inhibitors. At the ceiling ratio of 160,000 THB/QALY (4,434.59 USD/QALY), the probability that DPP-4 inhibitors are cost-effective compared to SFU was less than 10%. Conclusions: Compared to SFU, DPP-4 inhibitor monotherapy is not a cost-effective treatment for people with T2DM and CKD in Thailand.